Nippon, a charted survey of Japan 1986/87 (Konkusei- Sha, 1986)
This book has been published roughly in the same style. Nihon Kokusei-Zue, founded by the late Tsuneta Yano, is annual publication intended for young Japanese which describle the present condition of the society using a lot of statistical charts and tables,...